PENCARIAN AKAR KOMPLEKS POLINOMIAL DENGAN PEMROGRAMAN DELPHI MENGGUNAKAN METODE BAIRSTOWS - Ezrifal Sany (JURNAL AKADEMIKA)
In the field of Engineering and physics often encountered in the form of mathematical models of complex roots of equations. In the completion of the complex roots of the equation often appears that the problem can not be processed, and therefore need much to solve the equations that determine the roots of a complex equation. In making this system using the method Bairstows. By using this system known how many methods theuseof efficiencyof inconducting settlement Bairstows equation has complex roots elements. This system can be used as a means of calculating the completion of a complex system of equations that has an element of the real numbers.